Plant Therapy Sebagai Resiliensi Stres Bagi Pasien Covid-19 - Shinta Ath-Thariq Apriari; Mohammad Salehudin (Universitas Pendidikan Ganesha, 2022)
Such significant changes due to the emergence of Covid-19 can have an impact on increasing stress levels for Covid-19 patients undergoing isolation. Isolation that limits space for movement and coupled with difficulty in adapting creates pressure that leads to stress for Covid-19 patients. Resilience is present as a shield in the face of stress during isolation by utilizing plant therapy media (plant therapy). Plant therapy has a number of psychological and physical benefits as well as ecological sustainability. This study uses a qualitative method through a descriptive approach. The data collection technique for this research was through telephone interviews, WhatsApp chat and google forms with long answers for Covid-19 patients undergoing isolation. The analysis used in this study is the analysis of Miles & Huberman. This study aims to determine the benefits of plant therapy (plant therapy) as a tool that forms the resilience of Covid-19 patients in dealing with stress during isolation. It is hoped that this research can contribute to developing stress resilience and also maintaining ecological sustainability. Abstrak: Perubahan signifikan akibat munculnya Covid-19 tersebut dapat berdampak pada meningkatnya tingkat stres pasien Covid-19 yang menjalani isolasi. Isolasi yang membatasi ruang gerak dan ditambah dengan kesulitan beradaptasi menciptakan tekanan yang berujung pada stres bagi pasien Covid-19. Resiliensi hadir sebagai tameng dalam menghadapi stres selama isolasi dengan memanfaatkan media terapi tanaman (plant therapy). Terapi tanaman memiliki sejumlah manfaat psikologis dan fisik serta keberlanjutan ekologis. Penelitian ini menggunakan metode kualitatif melalui pendekatan deskriptif. Teknik pengumpulan data untuk penelitian ini adalah melalui wawancara telepon, chat WhatsApp dan google form dengan jawaban panjang untuk pasien Covid-19 yang menjalani isolasi. Analisis yang digunakan dalam penelitian ini adalah analisis Miles & Huberman. Penelitian ini bertujuan untuk mengetahui manfaat terapi tanaman (plant therapy) sebagai alat pembentuk ketahanan pasien Covid-19 dalam menghadapi stres selama isolasi. Diharapkan penelitian ini dapat berkontribusi dalam mengembangkan ketahanan terhadap stres dan juga menjaga kelestarian ekologi.